Faktor – Faktor Yang Berhubungan Dengan Kejadian Diare Pada Balita Di Puskesmas Rejosari Kota Pekanbaru - Alfianur Alfianur; Toni Zayendra; Tria Monja Mandira; Ritta Farma; Nurwulan Adi Ismaya (Edu Masda Journal, 2021)
Diarrhea may be fatal in part if it is not treated seriously, it because half of infant body composed mostly of water and is very sensitive to dehydration. The study aimed to determine all factors correlated to diarrhea incidence in toddlers. This is quantitative study and used correlation, this crossectional approach study design. Sample was 72 parents of children under five years. This study used accidental technique. This research was done in June until May 2016 in Puskesmas Rejosari Pekanbaru. A measuring instrument that used questionnaire. The analysis used univariat and bivariate. The data was analyzed used Chi-Square. The findings revealed a connection between a mother’s knowledge of diarrhea in toddlers (p=0,001), a mother’s habit of washing her hands with diarrhea in toddlers (p=0,002), and garbage disposal with diarrhea in toddlers (p=0,002). This research recommends for the next research to develop more the result of the research using different variable like the role of the health worker to diarrhea incident in toddler.